Perception on the Conservation Status of Primate Species in Maiha Local Government Area, Adamawa State - S, Bode A.; R, Umar M.; Y, Adamu M. (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2025)
This study investigates the status of primate species, the drivers of their decline, and local residents' perceptions regarding primate conservation in Maiha Local Government Area. Data were obtained through both primary and secondary sources. Primary data were collected using structured questionnaires administered through simple random sampling, while secondary data were sourced from journals, proceedings, books, brochures, and manuals. Descriptive statistics were used for data analysis. Primate species status was assessed through direct sightings, ecological indices, and interviews with key stakeholders, including forest and wildlife officers, traditional leaders, hunters, bushmeat sellers, and pastoralists. Six primate species were identified during the study period. Of these, two species, Baboon and Red Patas Monkey were found to be common, Tantalus Monkey was categorized as rare, and three species, Chimpanzee, Putty-nosed Monkey, and Mona Monkey were considered locally extinct. The primary factors contributing to primate decline included hunting (27.6%), farming (22.1%), logging (13.6%), grazing (10.5%), wildfire (8.3%), poverty (6.3%), population increase (3.4%), settlement (3.0%), infrastructure development (2.8%), and insurgency (1.9%). Respondents generally perceived primates as important and expressed willingness to support conservation efforts. Reasons for support or opposition to conservation were also documented. The study recommends enhanced conservation education, long-term monitoring of primate populations, diversification of income-generating activities to reduce forest dependency, and the establishment of protected areas to support primate and wildlife conservation.